Effect Of Perceived Hindrances In The Relationship Between Technlogy Factors And Online Learning Among College Students In Pampanga - Angela E Pineda; Jill Lovely S. Hipolito; Pamela Marie B. Liwanag; Helen Grace Angeles; Ayodele Oluyinka Solomon; Jusfer Sarsoza (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Challenges and obstructions in online learning are inevitable for students. Hence, government, faculty members, and students should understand the hindrances and other factors influencing online learning. Objectives: This study aims to determine the significant effect of perceived hindrances in relation to technology factors affecting the students' online learning. Design: This study is a Quantitative research wherein data is gathered through an online survey questionnaire or a Google form in accordance with TAM factors, which include perceived hindrances, perceived ease of use, and perceived usefulness that influence college students' engagement in online learning. The instrument was verified by five experts to ensure its validity and reliability of the survey questionnaire. The researchers conducted a pilot study statistically with twenty-five respondents from various schools and institutions in Pampanga to support the expert validation. The participants are college students who currently enrolled from various schools in Pampanga, Philippines. Smart PLS 3 was used to gain a better overview of the two hundred and fifty responses and to identify those supported and unsupported outcome. Provided by the Smart PLS software, given the bootstrap method, P value of less than 0.05 is a supported outcome. In presenting the quality of the constructed model R square is given by the algorithm method where a round 52% total variance is presented. As a result, the collected data and findings were deemed to be reliable and significant. Other factors that supported the constructed hypothesis has a significant effect to college students' online learning. The findings and recommendations of the study will serve as a reference for better online learning engagement as well as a solution for preventing students from being hindered and for creating an active online learning engagement